Towards an unknown Marx :a commentary on the manuscripts of 1861-63 - Dussel, Enrique D. (Routledge, 2001)
This book is the first complete commentary on Marx's manuscripts of 1861-63, works that guide our understanding of fundamental concepts such as 'surplus-value' and 'production price'.